Integrasi Halal Assurance System 23000 & ISO 22000 dalam Perspektif Tauhid Ismail Raji al-Faruqi - Ariza Qanita; Helmi Syaifuddin (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2023)
The integration of HAS 23000 and ISO 22000:2018 is very important as a standardization of food product safety and halal management. The integration of HAS 23000 and ISO 22000:2018 is also in accordance with the idea of ​​integration of science and religion by Ismail Raji al-Faruqi. This research aims to develop the concept of an integrated management system between HAS 23000 and ISO 22000:2018 based on the tauhid principle of Ismail Raji al-Faruqi. This research used a descriptive qualitative approach with a literature study. The data used is secondary data in the form of books and articles according to the research topic. The integration of the eleven clauses of HAS 23000 and ISO 22000:2018 produces nine new clauses. That is organizational policies, management processes, planning activities, support processes, material analysis, operational activities, product analysis, control and evaluation and improvement strategies. The integration is also in accordance with the tauhid principle by Ismail Raji al-Faruqi which is developed in five aspects, namely the oneness of God, the unity of creation, the unity of truth and knowledge, the unity of life and the unity of humanity. The integration of HAS 23000 and ISO 22000:2018 has several advantages such as increasing positive business image, increasing consumer trust and satisfaction, expanding product marketing in the international market, saving time and costs, reducing risk and reducing duplication of management tasks so that they are more effective.